When Does Visual Perceptual Grouping Affect Multisensory Integration? - CHAN, JASON (The Psychonomic Society, 2004)
Several studies have shown that the direction in which a visual apparent motion stream moves can influence the perceived direction of an auditory apparent motion stream (an effect known as crossmodal dynamic capture). However, little is known about the role that intramodal perceptual grouping processes play in the multisensory integration of motion information. The present study was designed to investigate the time course of any modulation of the cross-modal dynamic capture effect by the nature of the perceptual grouping taking place within vision. Participants were required to judge the direction of an auditory apparent motion stream while trying to ignore visual apparent motion streams presented in a variety of different configurations. Our results demonstrate that the cross-modal dynamic capture effect was influenced more by visual perceptual grouping when the conditions for intramodal perceptual grouping were set up prior to the presentation of the audiovisual apparent motion stimuli. However, no such modulation occurred when the visual perceptual grouping manipulation was established at the same time as or after the presentation of the audiovisual stimuli. These results highlight the importance of the unimodal perceptual organization of sensory information to the manifestation of multisensory integration.
PUBLISHED
Keywords: Psychology